Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.

Electrochemical synthesis of a ternary transition metal sulfide nanosheets on nickel foam and energy storage application - Sahoo, Surjit; Naik, Kusha Kumar; Late, Dattatray J.; Rout, Chandra Sekhar (Journal of Alloys and Compounds, 2017)
We report growth of nickel cobalt sulfide (NCS) ultrathin nanosheets directly on Ni foam substrate by a facile and novel electrodeposition method. The as-prepared NCS sample is used as an electrode material for supercapacitor application due to their large electrochemically active surface area and interconnected nanosheet channels for the facilitation of ion transportation. The NCS nanosheets possess enhanced electrochemical performance in terms of fast and high reversible faradaic reactions characterized by prominent oxidation and reduction peaks. NCS nanosheets showed an ultrahigh specific capacitance of 1712 Fg(-1) at a current density of 1 Ag-1 with excellent cyclic stability. The excellent supercapacitor performance of NCS nanosheets can be attributed to its rich redox reactions as well as high transport rate for both electrolyte ions and electrons. (C) 2016 Elsevier B.V. All rights reserved.